The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fevo.2021.638870
|View full text |Cite
|
Sign up to set email alerts
|

Using Sapelli in the Field: Methods and Data for an Inclusive Citizen Science

Abstract: The Sapelli smartphone application aims to support any community to engage in citizen science activities to address local concerns and needs. However, Sapelli was designed and developed not as a piece of technology without a context, but as the technical part of a socio-technical approach to establish a participatory science process. This paper provides the methodological framework for implementing and using Sapelli in the field. Specifically, we present the role of Sapelli within the framework of an “Extreme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…CCS programmes require ecological and sound facilitation expertise from researchers, careful consideration and long-term planning. The approach is used in the Global South 205 and the Global North 232 , including the Arctic 233 , in environmental justice 234 and other community-based initiatives. The Community-based Monitoring Library provides bestpractice examples from the Arctic and lessons learnt for practitioners.…”
Section: Box 1 | Community-led Citizen Science In Ecology and Environ...mentioning
confidence: 99%
“…CCS programmes require ecological and sound facilitation expertise from researchers, careful consideration and long-term planning. The approach is used in the Global South 205 and the Global North 232 , including the Arctic 233 , in environmental justice 234 and other community-based initiatives. The Community-based Monitoring Library provides bestpractice examples from the Arctic and lessons learnt for practitioners.…”
Section: Box 1 | Community-led Citizen Science In Ecology and Environ...mentioning
confidence: 99%
“…Technology and more widely literacy and ability barriers must be addressed. Moustard et al [ 11 ] observed that rural communities and local participants may be non-literate but are most ecologically literate. Their involvement was facilitated through use of a smartphone application based on Sapelli, an open-source configurable icon-driven user interface for data collection across language and literacy barriers [ 12 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In recent years, the core of Citizen Science work has aimed to empower communities to build, design and then utilise their own research potential. As explored elsewhere (Moustard et al 2021), a majority of Citizen Science projects have focussed on a highly specific problem or issue identified by outside 'experts'. The gathering of data is then used to build an evidential base for or against a certain course of action -such as noise pollution, illegal logging, community rights to land, or similar (Bishop 2021(Bishop et al 2021Senabre Hidalgo et al 2021).…”
Section: Harnessing Small-holder Farmer's Capacities: a Citizen Scien...mentioning
confidence: 99%
“…The co-design process for the Sapelli Project followed that outlined in Moustard et al (2021) and was built on the core principle of Free Prior and Informed Consent (FPIC) and the development of a community protocol to govern the collaboration. This not only involved providing participants with all of the information on the proposed project, but also the active collaborative exploration between researchers and community members to understand potential positive and negative impacts of the project's outcomes.…”
Section: Engagement and Participatory Designmentioning
confidence: 99%